System determinants of unequal economic development of globalized world - ZVARYCH, Roman (Scientific journal «World of Finance», 2019)
Introduction. Globalization has accelerated the transformation of authoritarian societies into the perception of individual elements of the liberal-market model. It created favorable conditions for their cooperation with developed Western countries; stimulated economic modernization; and attracted countries to world economic processes. Positive shifts in the development of developing countries are associated with high rate of growth. But on the other hand, globalization left national states little chance to preserve their own economic, political and cultural sovereignty and strengthened their dependence on the developed world.Purpose. Purpose of the article is research of the unequal economic participation and divergence of economic inequality in developing countries and estimation of their impact on the uneven development of the world.Methods. The method of content formalization the development, growth and convergence of developing countries is used; hypothetical-deductive method in evaluating the level of preindustrial inequality in the world is used; systematic approach to analyze income gap per capita between rich and poor countries is used; hypothesis method for poverty reduction ways and geopolitical risks elimination is used.Results. The research is focused on development, growth and convergence of developing countries in the world economy. It is estimated the level of preindustrial inequality and it is established the starting point of its occurrence in the world. The developing and industrialized world is concentrated in dozens of countries where economic growth was associated with structural changes in production and employment. The research showed a gap in income per capita between rich and poor countries. The exclusion of the least developed countries is a key factor of international inequalities in the world as a whole and within the developing regions. It is defined the share of people below the poverty line and the level of its influence on world development. If rapid growth has led to human development and social progress in some countries, then in much more countries this growth has not provided development. It is explored the poverty reduction measures, non-economic factors and geopolitical risks that can destroy the further growth of developing countries.Conclusion. In a context of structural change, the development of the global economy will largely depend on the growth rates of developing countries. Despite the growing of economic power, developing countries can face certain specific problems associated with the pursuit of rapid economic growth. For economic development, developing countries should eradicate poverty, create jobs and inclusive growth. This sustainable way of developing mobilizes human resources of developing countries. The spread of education is the basis of the development of countries that industrialized late. Infrastructure, both physical and social, is the basis for the earlier stages of industrialization. Developing countries should strive to combine economic growth with human development and social transformation. This requires the creative interaction between the state and the market over the dominance of the market model.